Sistem Pendukung Keputusan Pemilihan Obat Demam Terbaik Menggunakan Metode Simple Additive Weighting (Saw) - Hendri Maradona; Dona; Mi’rajul Rifqi; Kiki Yasdomi; Nasrizal (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Decision Support System (DSS) or Decision Support System (DSS) is a system that is able to provide problemsolving and communication skills for problems with semi-structured and unstructured conditions. Along with the development of technology and information, as if it has created a new standard that must be met in the world of health. With the rapid development of technology, it is encouraging to build a computer-based system for the selection of fever drugs in pharmacies, using this kompeter system can facilitate the search for the determination of appropriate drugs. In making this system using the Simple Additive Weighting (SAW) method. With this method can make it easier in calculating the value of fever medication that is suitable for customers, in this case taken from the Apotek Semangat. On the results of the output in this system will display the value and data name of the drug in accordance with the customer that has been inputted by the admin in charge. With the use of this system, it will certainly be able to help pharmacies not give greetings in administering fever medicines